A experiência de estigma e discriminação em homem que faz sexo com homens (HSH) vivendo com HIV - Garcia, Roberto (2012)
Since its beginning, the Aids epidemic has established a series of social representations which hampers the daily life of men who have sex with men (MSM) living with HIV, who see themselves as doubly stigmatized due to their sexual orientation. The main objective of this study is observing the experience of stigma and discrimination in man who has sex with men living with HIV. With this ample target in mind, the specific objectives are: firstly, to observe the possible implications that HIV may cause on seropositive individuals as regards to perception of disease, self-perception as infected, social network, sexual orientation and involved contexts of vulnerability; and secondly, to observe the differences in the experiences of HIV-positive MSM through diagnosis disclosing to the social network by individuals infected before chronification and those infected after chronification. Based on the Theory of Social Representations, this work adopts the technique of the Discourse of the Collective Subject (LEFEVRE & LEFEVRE, 2010), a method of quali-quantitative nature. The corpus of the study is formed by a sample of thirty three MSM living with HIV, between 20 and 60 years of age, from a municipal clinic at the Greater São Paulo. The results reveal a high index of stigma and discrimination, manifested by sensations of fear, rejection, constant state of alert and guilt, in a social network that is fragile and unreliable. These high indexes were reflected in the increase of vulnerability of these individuals, demonstrated by the non-use of condom, by the fear of aggression, by the discrimination and the isolation, among others